Pengaruh Stres Dan Kelelahan Kerja Terhadap Kinerja Guru SMPN 2 Sukodono Di Kabupaten Lumajang - Zainul Hidayat (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This research is a quantitative research looking associative relationships that are causal or research that is asking a relationship between two or more variables and is causal. The research aims to obtain evidence of the effect of stress and fatigue on the performance of teachers at SMP Negeri 2 Sukodono in Lumajang either partially or simultaneously. This study tested the hypothesis that there is a significant effect of stress on teacher performance, there is a significant effect of fatigue on teacher performance, and there is stress and fatigue pengarus significant work simultaneously on teacher performance SMP Negeri 2 Sukodono in Lumajang. The study of 30 respondents using multiple linear regression analysis is that there is a significant effect of work stress on employee performance, there is a significant effect of fatigue on employee performance, and there is stress and fatigue pengarus significant work simultaneously on teacher performance in SMP Negeri 2 Sukodono Lumajang. Simple linear regression function generated is Y = 47.395 to 2.183 X1 - X2 2.525. The coefficient of determination shows that 17% of employee performance can be explained by the variable stress and work fatigue, while the remaining 83% of teacher performance is influenced by other variables not examined in this study. Limitations of this study were only examined work stress and fatigue as a factor affecting the performance of the teacher, while the other variables that can affect a teacher's performance is expected to be further investigated by researchers indifferent periods and places.